Normal palpebral anthropometric measurements in Uygur population: a cross-sectional study - Jiang, Aixin; Zhang, Fan; Kurbana, Mayila; Xiong, Ke; admin, (Journal of the Pakistan Medical Association, 2023)
Objective: To provide a normative palpebral database for the Uygur subjects to determine norms that may contribute to the diagnosis and prognosis of eyelid diseases. Method: The cross-sectional study was conducted from March to May 2021 at the First People’s Hospital of Kashi, China, and comprised Uygur subjects of either gender aged 18-70 years. The slant, height and width of the palpebral fissure, vertical brow-upper lid distance, intercanthal distance, pupillary distance, brow height, crease height and levator function were measured. Data was analysed using SPSS 22. Results: Of the 335 subjects having mean age 41.41±14.53 years, 165(49.3%) were males with mean age 41.08±14.23 years and 170(50.7%) were females with mean age 41.74±14.85 years. There were 107(31.9%) subjects aged 18-30 years, 115(34.3%) aged 31-50 years and 113(33.7%) aged 51-70 years. Mean palpebral fissure width and margin reflex distance of the palpebrae were significantly different in terms of gender (p<0.05). Age was also a significant factor on several counts (p<0.05). Conclusions: Anthropometric measurements of eyelid in Uygur subjects indicated certain peculiarities. Key Words: Eyelid, Palpebral morphology, Measurement, Epicanthus, Blepharoplasty.